A PIMR-Type Repetitive Control for a Grid-Tied Inverter with Frequency Adaptation - Qiangsong Zhao; Sainan Chen; Xiaohui Lu (International Conference on Advanced Mechatronic Systems, 2018)
A proportional-integral multiresonant type repetitive control (PIMR-type RC) has not only a better harmonics suppressing performance but also a faster error convergence rate. However, reference frequency fluctuation in a large range will significantly decrease the harmonics suppressing performance of PIMR-type repetitive control. In this paper, a PIMR-type repetitive control with frequency adaptation is proposed to cope with the frequency fluctuation. The improved PIMR-type repetitive control uses fractional delay filter which can be approximately realized by finite impulse response (FIR) filter. The varying fractional delay filters ensure that the resonant frequencies can match the actual reference frequency and harmonic frequencies. The simulation results show that the proposed PIMR-type repetitive control can track grid reference signal and suppress harmonic signals, and have good error convergence rate under grid frequency fluctuation.